(3dYdg JaSjQ GdHjVGhjs - (3eLghds
(3ChdgG (B:s
(3ShQI GdfHC ecjI hgj CQHYhf hEMOi hCQHYhf BjI, hKdGKI hSHYhf cdeI, hSHY eFI hSHYhf MQaGs
(3BNQgG (B:s
(3bGdg GdCfHGQj hCYjPceG HcdeGJ Gddg GdJGeI ef cd TjWGf hgGeI hef cd Yjf dGeI hcdGe GdNGdb GdPj gh BjI hMLI deMeO Udi Gddg JYGdi Ydjgs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs